Development of effective human factors interventions for aviation safety management - Chan, Wesley Tsz-Kin; Li, Wen-Chin (Frontiers in Public Health, 2023)
In aviation, the safety management system (SMS) is an organizational tool for systematic risk management. Although the SMS applies to components both within and external to the organization, current methods in identifying and categorizing safety conditions are predominantly restricted to the confines of the organization. Risk assessments are affected by subjective differences in interpretation, with professional experience and expertise known to influence safety attitudes. To evaluate the effects of experience factors on risk management and to account for the influence of professional exposure on SMS processes, the present study compared the classification of active failures and latent human factors conditions between pilots with high and low experience, as measured by total flight hours (TFH). Results from 144 valid responses revealed differences in the attribution of human factors conditions, with the high experience group more inclined to classify conditions to supervisory and organizational levels and finding more targeted paths of associations between latent conditions. In contrast, the low experience group presented a greater number of associations between categories, showcasing a more fragmented approach to safety culture with influences by peculiar characteristics such as ability to handle stress. As these between-group differences can exist at the interface between system components, the results suggest that human factors interventions targeting the system-wide concerns, influences, and actions originating from both within and external to the organization will be the most effective for SMS.